2010
DOI: 10.1098/rsta.2010.0091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fatigue on force fluctuations in knee extensors in young adults

Abstract: This study investigated the hypothesis that fatiguing exercises led to increased force fluctuations during submaximal isometric knee extensions and to decreased accuracy and steadiness in the time and frequency domains. Sixteen young adults (eight males, eight females) were tested, in a seated posture with 90°knee flexion, to assess their ability to reproduce target extensor torques set at 15 per cent and 20 per cent of their maximum voluntary isometric contraction, both before and after fatiguing exercises. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 52 publications
(109 reference statements)
5
39
0
Order By: Relevance
“…Increases in muscular cocontraction and stiffness with force variability spurred us to examine the relationship between w and force variability. Similar to Reeves et al (2008) and Singh et al (2010), we found that force variability measures in the time domain (F CV ) increased with fatigue for all contraction intensities. Furthermore, we found that greater F CV corresponded with increased cocontraction intensity for 8 of the 10 windows.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Increases in muscular cocontraction and stiffness with force variability spurred us to examine the relationship between w and force variability. Similar to Reeves et al (2008) and Singh et al (2010), we found that force variability measures in the time domain (F CV ) increased with fatigue for all contraction intensities. Furthermore, we found that greater F CV corresponded with increased cocontraction intensity for 8 of the 10 windows.…”
Section: Discussionsupporting
confidence: 66%
“…We found that F MPF decreased with fatigue and contraction intensity. Singh et al (2010) in F MPF with contraction intensity, but found that F MPF increased with fatigue. Differences between our studies include the examined joint (elbow vs. knee) and tested contraction intensities (40%, 70%, and 100% vs. 15% and 20%).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Here, stability parameters not only provide information regarding the noise present in the motor task performance, but also explicitly quantify the performance of the dynamic error correction. On the other hand, variability during specific tasks results from noise present in the motor task and in the environment [56][57][58]. In addition, variability will increase at a given noise level when error corrections are less effective.…”
Section: The Assessment Of Gait Stabilitymentioning
confidence: 99%
“…Levels of investigation range from the tissue level, as in 'Trabecular bone remodelling simulation considering osteocytic response to fluid-induced shear stress' (Adachi et al 2010) and 'In silico design of treatment strategies in wound healing and bone fracture healing' (Geris et al 2010), to the whole organ, as in 'Predicting the yield of the proximal femur using highorder finite-element analysis with inhomogeneous orthotropic material properties' (Yosibash et al 2010) and 'Mechanical testing of bones: the positive synergy of finite-element models and in vitro experiments' (Cristofolini et al 2010) or even the entire organ system, as in 'Influence of fatigue on the simulated relation between the amplitude of the surface electromyogram and muscle force' (Dideriksen et al 2010) and 'Effect of fatigue on force fluctuations in knee extensors in young adults' (Singh et al 2010). All papers share the integrative approach that is characteristic of VPH research.…”
Section: Introductionmentioning
confidence: 99%